A systems-based approach to injury prevention for the strength and conditioning coach - Howe, L. P.; Waldron, M.; Read, P. (Strength and Conditioning Journal, 2017)
Participation in sport exposes athletes to an inherent risk of injury. To develop a comprehensive injury prevention program, strength and conditioning coaches must conduct a thorough needs analysis to establish the risk of injury, identify mechanisms and risk factors for injury, select relevant screening tests, and design targeted interventions based on the athlete's results. Using a systems-based approach presented herein, this article provides an overview of the process that coaches must undertake to develop effective injury prevention programs.